Descripción etológica del gusano blanco del cultivo de papa (Solanum tuberosum) de variedad súper chola, en el laboratorio Ceasa, sector Salache, provincia de Cotopaxi período 2015 - Fajardo Jaguaco, José Fernando (2016)
The research was conducted in the entomology laboratory at the Technical University of Cotopaxi, Cotopaxi Province, the objectives of this study were: to determine the life cycle, habits, and behaviors of Premnotrypes vorax under laboratory conditions. The taxonomic description of plague in the study was determined in the laboratory phase: Classification: Coleoptera, Family: Curculionidae, Subfamily: Curculionoidea, Genus: Premnotrypes, Species: Vorax. The life cycle of Premnotrypes vorax is 112,4 days according to the research stage….